Intergovernmental Relations in Chile - Navarrete-Yanez, B (Springer, 2023)
The central, regional, provincial and local territorial model in Chile was designed and implemented under the authoritarian Pinochet regime in 1980 and remained unchanged for fifty years. The direct election of regional governors in 2021 and the rejected constitutional proposal of 2022 are generating a new “road map” in the discussion of Intergovernmental Relations (IGR). Through a review of the press and available literature, two scenarios that will influence this discussion are analyzed: the tension between the regional governor and the presidential delegate, and the model of autonomous territorial entities -regions, municipalities and indigenous communities- proposed by the Constituent Assembly. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.